(untitled) (Revista Psicología y Sociedad, 2025)
Within the context of primary health care and the innovation processes generated by research results, the conceptual framework underlying the development of the Apprevenir mobile application and digital ecosystem is presented. The Luis Amigó Catholic University, located in Medellín, Antioquia, owns this application. The purpose of this application is to develop universal prevention actions for addictions derived from the use of psychoactive substances and other behavioral addictions within the framework of primary health care policy and considering advances in research processes developed within projects related to topics such as addictions, mental health, and e-health. This digital ecosystem is aimed at different sectors of the population, although it has greater experience with adolescents, youth, and young adults in university settings.